Evaluating the Effectiveness of Smart Inverter Control for Solar-Powered EV Charging Stations - Vishal S. Wadkar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Solar-powered electric vehicle (EV) charging stations have gained significant attention as a sustainable solution to the growing demand for clean transportation. The integration of smart inverter control technology in these charging stations has shown promise in optimizing power flow and improving the overall efficiency of the charging process. This paper presents a comprehensive evaluation of the effectiveness of smart inverter control for solar-powered EV charging stations. The study examines the impact of smart inverter control on key performance indicators, including charging efficiency, grid integration, and cost-effectiveness.